Implementasi Rutinan Ziarah Wali Sebagai Media Dakwah Pembentukan Karakter Santri Pondok Pesantren Al Hidayat Lasem - Farida Isroani (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Character or morality is very important in Islamic education. There are many ways or media for character education for children in Islamic boarding schools, one of which is by implementing the guardian pilgrimage routine. The guardian pilgrimage is carried out to instill the religiosity of children as well as to increase their spiritual nature. In addition, guardian pilgrimage activities can also be applied character education for children when they mingle with the surrounding community. The objectives to be achieved in this study are to answer the formulations that arise, namely: To find out the media for character education of students through the guardian pilgrimage routine at the Pondok Pesantren Al Hidayat Lasem, to find out the implementation of the guardian pilgrimage routine as a medium for character education at the Pondok Pesantren Al Hidayat Lasem, to knowing the value of character education through the guardian pilgrimage routine at the Pondok Pesantren Al Hidayat Lasem The type of this research is qualitative research, the research was conducted by taking 12 pesantren administrators and 3 students as respondents. Data collection methods were obtained from the results of observations, interviews, and documentation. The results of this study indicate that: The media for character education for students through the guardian pilgrimage routine at the Pondok Pesantren Al Hidayat Lasem is carried out with several character education media, namely: Habituation, Exemplary, fostering student discipline, practice. The implementation of the guardian pilgrimage routine as a medium for character education at the Pondok Pesantren Al Hidayat Lasem is: through Dhikr and Tahlil, Telling stories and showing the history of the guardian, showing the legacy of the guardian. The value of character education through the guardian pilgrimage routine at the Pondok Pesantren Al Hidayat Lasem, namely: The value of discipline character, The value of the character of curiosity, The value of the character of responsibility, The value of polite character, The value of religious character.